1970
DOI: 10.1017/s002202990001342x
|View full text |Cite
|
Sign up to set email alerts
|

The release of peptides and glycopeptides by the action of heat on cow's milk

Abstract: SummaryThe release, as a result of heat treatment on cow's milk, of peptides and glycopeptides which are soluble in the 12% trichloroacetic acid (TCA) filtrate of the milk has been studied. The results showed that the amount of peptides released increased with temperature and duration of the heat treatment. There were differences between milks in their response to a given heat treatment. Glycopeptides were released at temperatures as low as 50 °C but not at 37 °C. A comparison was made of the glycopeptides rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…When Lactobacillus casei grow at 34°C in sterilized skim milk in the absence of 1% peptone and of the controlled of culture acidity, and with fortification of the media with 1% peptone of the controlled culture acidity, the population density was several times higher in culture supplemented with peptone and control of culture acidity, reached a population density of 90x10 6 CFU/ml, compared with 11x10 6 CFU/ml by the same strain being grown as a control. This medium proved to be superior for lactic acid production Figures 5 and 6 these results agreed with those reported by Ismail (1991 b), Hindle and Wheelock(1970), and Thandon and Ganguli (1972).…”
Section: Resultssupporting
confidence: 90%
“…When Lactobacillus casei grow at 34°C in sterilized skim milk in the absence of 1% peptone and of the controlled of culture acidity, and with fortification of the media with 1% peptone of the controlled culture acidity, the population density was several times higher in culture supplemented with peptone and control of culture acidity, reached a population density of 90x10 6 CFU/ml, compared with 11x10 6 CFU/ml by the same strain being grown as a control. This medium proved to be superior for lactic acid production Figures 5 and 6 these results agreed with those reported by Ismail (1991 b), Hindle and Wheelock(1970), and Thandon and Ganguli (1972).…”
Section: Resultssupporting
confidence: 90%
“…No low molar mass peptides from C-terminal fragment of β-casein, N-terminal of α s" -casein or C and N terminal of α s# -casein were detected. Moreover, no low molar mass glycosylated peptide from κ-casein, as reported by Hindle & Wheelock (1970), was detected. The release of phosphopeptides κ-CN f(149-169), β-CN f(1-16), β-CN f(1-17) and β-CN f(1-18) indicated that the phosphorus released during heating was not entirely inorganic.…”
Section: Peptide Identification By Rp-hplc Coupled To Esi-ms\msmentioning
confidence: 69%
“…During sterilization of milk or dairy products, increase in NPN fraction is a biochemical modification described and acknowledged by many authors (White & Davies, 1966 ;Hindle & Wheelock, 1970 ;Lorient & Alais, 1970 ;Saidi & Warthesen, 1993 ;Hustinx et al 1997 ;Morales & Jime! nez-Pe!…”
Section: Soluble Nitrogen Content and Fluorescence Intensity Of The 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Glycopeptides have been found in milk at temperatures above 50°C (Hindle and Wheelock 1970), and peptides similar to macropeptides from chymosin (EC 3.4.23.4) hydrolysis are produced in milk heated to 120°C for 20 min (Alais et al 1967). Under severe ultra-high-temper-ature pasteurization conditions (up to 154.4 °C for 9 sec), casein is solubilized (Morgan and Mangino 1979).…”
Section: Caseinsmentioning
confidence: 99%